Dataset Kinerja Guru Multikultural dalam Perspektif Etnopedagogi: Budaya Organisasi, Motivasi, dan Komunikasi Interpersonal - Galih Istiningsih; Rasidi; Anang Amiruddin Nugroho (Journal of Innovative and Creativity, 2026)
Multicultural schools reflect diversity that requires teachers to demonstrate professional performance beyond pedagogical competence, including organizational culture, motivation, commitment, and interpersonal communication. This study aimed to document and examine multicultural teacher performance through the development of a valid and reliable empirical dataset grounded in local wisdom–based organizational culture. A quantitative survey design was employed involving 100 multicultural teachers from six schools at elementary, junior high, and senior high levels in Indonesia. Data were analyzed using factor analysis, correlation, and regression techniques. The findings reveal that organizational culture and work motivation, particularly incentive motivation, significantly influence teacher performance, while interpersonal communication and teacher commitment function as supporting factors. This study concludes that strengthening local wisdom–based organizational culture is essential for improving multicultural teacher performance and that the resulting dataset provides a contextual reference for further research and educational policy development.